Application of UV absorbance and electron-donating capacity as surrogates for micropollutant abatement during full-scale ozonation of secondary-treated wastewater. (1st February 2022) - Walpen, Nicolas; Joss, Adriano; von Gunten, Urs
Highlights: An on-line analyzer was developed to continuously measure UV absorbance and EDC. Values before and after ozonation of secondary-treated wastewater were monitored. Residual EDC and UV absorbance responded to changes in the ozone dose. Compared to the UV absorbance, the EDC responded more sensitive to low ozone doses. Residual EDC and UV absorbance are suitable surrogates for micropollutant abatement. Abstract: Ozonation of secondary-treated wastewater for the abatement of micropollutants requires a reliable control of ozone doses. Changes in the UV absorbance of dissolved organic matter (DOM) during ozonation allow to estimate micropollutant abatement on-line and were therefore identified as feed-back control parameter. In this study, the suitability of the electron-donating capacity (EDC) as an additional surrogate parameter which is independent of optical DOM properties was evaluated during full-scale ozonation. For this purpose, a recently developed EDC analyzer was enhanced to enable continuous on-line EDC and UV absorbance measurements. During a multi-week monitoring campaign at the wastewater treatment plant of Zurich, Switzerland, specific ozone doses were varied from 0.13 to 0.91 mgO3 ⋅mgDOC −1 and selected micropollutants with different ozone reactivities were analyzed by LC-MS in conjunction with bromate analysis by IC-MS. In agreement with previous laboratory studies, the relative residual UV absorbance and EDC both decreased exponentially as a function of the specific ozone dose and, in comparison to the residual UV absorbance, residual EDC values showed a more pronounced decrease at low specific ozone doses ≤0.34 mgO3 ⋅mgDOC −1 . Logistic regression models allowed to estimate relative residual micropollutant concentrations in the ozonation effluent using either the residual UV absorbance or EDC as explanatory variable. Averaging those models along the explanatory variables allowed to estimate target values in relative residual UV absorbances and EDC for specific micropollutant abatement targets. In addition, both parameters allowed to identify conditions with elevated conversions of bromide to bromate. Taken together, these findings show that the integration of relative residual EDC values as a second control parameter can improve existing absorbance-based ozonation control systems to meet micropollutant abatement targets, particularly for treatment systems where low ozone doses are applied. Graphical abstract: Image, graphical abstract